If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36.86 = 7g + 3.54 Reorder the terms: 36.86 = 3.54 + 7g Solving 36.86 = 3.54 + 7g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7g' to each side of the equation. 36.86 + -7g = 3.54 + 7g + -7g Combine like terms: 7g + -7g = 0 36.86 + -7g = 3.54 + 0 36.86 + -7g = 3.54 Add '-36.86' to each side of the equation. 36.86 + -36.86 + -7g = 3.54 + -36.86 Combine like terms: 36.86 + -36.86 = 0.00 0.00 + -7g = 3.54 + -36.86 -7g = 3.54 + -36.86 Combine like terms: 3.54 + -36.86 = -33.32 -7g = -33.32 Divide each side by '-7'. g = 4.76 Simplifying g = 4.76
| -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 | | 11y-6=93 | | 6(6-6n-3)+3=8n+29 | | 13+3p=7-3p | | 3(x+2)=7(x-2) | | 0.625y-7=-2 | | -5(r+6)=-84 | | 3+5b=3b-1 | | 2[-(x-1)+4]=5+[-(6-7)+9x] | | -7-8r=1-6r-4 | | 8x+7x-66=110-7x | | 3.9=-log(x) |